Kedudukan Hukum PERMA Nomor 2 Tahun 2012 dalam Perspektif Sistem Peradilan Pidana (Studi di Pengadilan Negeri Kelas I Kupang) - Ballu, Nuriyani (Jurnal Media Hukum, 2018)
This study aims to determine the position and the application of criminal penalties in accordance with the Supreme Court Decree Number 2 of 2012 concerning Adjustment of Limitation of Minor Crime and Amount of Fine in the Penal Code from the Perspective of the Criminal Justice System. The nature of research is normative legal research. Data in the form of court decision was take from the Kupang District Court. Study was made against the theft case involving an accused named Yohamir Amtiran Alias Hamir Amtiran which is registered in the mentioned court numbered 205/ Pen.Pid / 2015 / PN.KPG. The accused person has been alleged for having stolen two watches, one with Giotana brand, silver-colored boxy, and another one with SEIKO brand, spherical gold. The theft was committed at night in a house owned by Indriani Listya Purwanti Indri alias Indri located in BSB Housing Complex, Puri Lontar Street, Oebufu Village, Oebobo Subdistrict, in Kupang. The economic value of the stolen properties is approximately Rp 1,500,000.00 (one million and five hundred thousand rupiahs). The accused was tried with the ordinary criminal proceedings and put under detention.Â  It is clear that the judges have not yet implemented the above mentioned Supreme Court Decree.